The Use Of Educational Technology by Pre-service Teacher In Jakarta - Faradilla, Diva Zulni; Santosa, Imam (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The Educational Technology Use Framework is a scientifically solid framework that defines what technology is used for students. Educational technology used has 5 categories. This framework aims to demonstrate what technologies students used and could improve and reinvent education and training. The teaching experience taught to created a controlled learning environment in which future teachers could put the ideas and practices gained. Based on 4 levels of pre-service teacher students who have analyzed, the researcher identified 54 students of English education in the data. In the overall calculation, there are 15 universities which are 30 private universities and 20 state universities. Then, 47 women and 7 men, the majority of respondents in this study were female students of English education. respondents (approximately 49 percent) in the category of Learning Tools and Learning Resources have the same number of Powerpoint technology and E-books. Students considered that E-books and Powerpoint technology could be useful and help in learning. The E-book serves as a means of learning and information media as well as facilitating the process of disseminating information. Powerpoint is an easy-to-use tool for discussing material.